"I Went into This as One Person, and Then Came Out a Totally Different Person": Native LGBTQ2S+ Young Adults’ Conceptions of Trauma - Schmitz, Rachel M. (Journal of interpersonal violence, 2022)
Intersecting sources of stigma influence harmful mental health outcomes for lesbian, gay, bisexual, transgender, queer, and Two-Spirit (LGBTQ2S+) young adults (YA) of color as they must manage multiple oppressions. Experiencing both mental health challenges and victimization, LGBTQ2S+ YA of color struggle with distinctive psychological traumas. There is a critical need to determine how certain groups of LGBTQ2S+ YA of color?s marginalized social statuses shape trauma understandings. Native LGBTQ2S+ people in general endure diverse forms of oppression and trauma, such as histories of colonialism, contemporary racism, sexism, homophobia, and classism. Understanding the subjective interpretations of violence and trauma among Native LGBTQ2S+ YA is needed to best meet their mental health needs. Through in-depth interviews with 13 Native LGBTQ2S+ YA between 18 and 24 years old, this study delineates processes of how an underrepresented, underserved group of rurally embedded YA conceptualize violent and traumatic life experiences within the context of their mental health. First, participants described their traumatic experiences as shaping persistent harmful mental health outcomes throughout their lives. Second, YA conceptualized trauma as pivotal moments that were profound and influential in their significance as a turning point in their lives. Finally, YA underscored multiple traumas as cumulative and complex in how they interacted to create distinctively harmful mental health challenges. Expansive conceptualizations of trauma can better inform understandings of trauma etiology and promote inclusive health services.